UPAYA UNTUK MENINGKATKAN KUALITAS HIDUP LANSIA MELALUI PERLAHAT (PERSATUAN LANSIA INGIN HIDUP SEHAT) DI DESA JATIDOWO KECAMATAN REJOTANGAN KABUPATEN TULUNGAGUNG - Erni Setiyorini; Ning Arti Wulandari; Yeni Kartika Sari (Community Development Journal, 2018)
Aging is a physiological process that causes a decrease in various organ functions, so that it is easy to experience non-communicable diseases both acute and chronic, besides that degenerative problems can reduce endurance so that they are susceptible to infectious diseases. Increased disease in the elderly, weak physical condition, minimal psychological support can cause changes in their quality of life. One of the factors that can influence the affordability of health services for the elderly is still uneven. Jatidowo villagers have the motivation to maintain their health so that they do not fall in sick condition, so that the PERLAHAT is suitable for application. The purpose of this community partnership program (PKM) is to maintain the health of the elderly to improve their quality of life. This activity was carried out in RW 1 and RW 2 Jatidowo Village, Rejotangan District, Tulungagung Regency. PERLAHAT activity is a simple examination carried out by cadres who were trained beforehand, health care activities in the form of gymnastics to maintain muscle strength and marawis to prevent dementia and conduct home visits for elderly who have experienced a decrease in conditions to provide psychological support. The method used in the effort to achieve these goals is by learning theory and practice, lectures, discussions and simulations. The results of the activity showed an improvement in the quality of life of the elderly, a decrease in morbidity, new case finding and an increase in the motivation of the elderly to attend the PERLAHAT activities.